1993
DOI: 10.1016/0266-7681(93)90203-r
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Swanson’s Silastic Arthroplasty of the Metacarpophalangeal Joints in Rheumatoid Arthritis

Abstract: 77 patients with rheumatoid arthritis, 62 female and 15 male, underwent metacarpophalangeal joint arthroplasty on 375 joints using the Swanson design silicone rubber spacer between 1976 and 1985. Retrospectively, 48 of these patients were evaluated by postal questionnaire and 35 of them also underwent objective assessment at intervals ranging from five to 14 years post-operatively. Objective variables recorded included range of active motion, recurrence of ulnar drift and radiographic appearances. Both in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(41 citation statements)
references
References 29 publications
3
38
0
Order By: Relevance
“…Other drawbacks include subluxation, bone erosion, loosening and implant abrasion (Hirakawa et al 1996). A key issue in the success of silicone-based implants lies in the appropriate design of the device mimicking the normal characteristics of the joint (El-Gammal & Blair 1993;Wilson et al 1993).…”
Section: Polymersmentioning
confidence: 99%
“…Other drawbacks include subluxation, bone erosion, loosening and implant abrasion (Hirakawa et al 1996). A key issue in the success of silicone-based implants lies in the appropriate design of the device mimicking the normal characteristics of the joint (El-Gammal & Blair 1993;Wilson et al 1993).…”
Section: Polymersmentioning
confidence: 99%
“…The Swanson silicone implant (Dow Corning, Midland, MI) has emerged as the preferred choice because of its flexibility and durability. 3 We chose to use the Swanson implant in this study because it is the most commonly used implant, having 75% of the US market for implants in the rheumatoid hand (personal communication, Wright Medical Technology, Arlington, TN). Despite the long-term use of Swanson implants, most published reports consist of uncontrolled retrospective case series that were based mainly on physical outcomes such as finger range of motion, grip strength, and degrees of residual ulnar drift.…”
mentioning
confidence: 99%
“…Studies using objective assessments have generally assessed the technical success of the surgery, assessing aspects such as joint alignment, 2 periprosthetic effects such as bone resorption, 3 implant loosening, 4 fracture, 5 functional outcomes such as range of motion and pinch and grip strength, 6 and postoperative complications such as infection or silicone lymphadenopathy. 7 Some studies have reported patients' performance in hand assessments.…”
mentioning
confidence: 99%